Servais Pinckaers and the Renewal of Catholic Moral Theology - Craig Steven Titus (Journal of Moral Theology, 2012)
Servais Pinckaers stands as a prominent figure in ressourcement theology that contributed to a renewal in moral theology. Shifting the subdiscipline to a foundation rooted in Scripture, patristics, and magisterial sources via his use of the historical method – as opposed to the casuistic modern manual tradition – Pinckaers worked to center his moral theology on the lines of the up-and-coming virtue-based theory and the dynamic of continuity between the Decalogue and the New Law.